Denaturation bubble-mediated two-stage isothermal nucleic acid amplification in a single closed tube. Issue 32 (31st March 2023) - Guo, Jinling; Li, Yang; Wang, Qing; Jiang, Qianqian; Zhang, Xinguang; Zhang, Peng; Ma, Cuiping; Shi, Chao
Abstract : A two-stage isothermal amplification method termed rolling cycle strand exchange amplification (RC-SEA) was established to accomplish ssRNA and dsDNA analysis using only one DNA polymerase in a single closed tube at a constant temperature. Abstract : Here, we established a two-stage isothermal amplification method comprising strand exchange amplification and hyperbranched rolling circle amplification, which only employed one DNA polymerase and was performed in a single closed tube at a constant temperature, providing a promising signal amplification strategy for accurate and rapid pathogen detection in the clinic.